MEDIA PEMBELAJARAN SEBAGAI ALTERNATIF MENINGKATKAN GAIRAH BELAJAR - Arista Selly Maharani; Salsa Umi Nasuha; Shilvi Rizky Maulida (Jurnal Bionatural, 2024)
Students' passion for learning is one of the influencing factors for students' learning achievement. With the emergence of enthusiasm for learning, students will have greater curiosity in learning. This is in line with the opinion of (Setiawan, 2021) Passion for learning is a person's (student) desire to acquire skills, knowledge and attitudes based on interest, curiosity and consideration. This research uses a literature review method (literature study) to determine learning media in building passion for learning. This method involves collecting, analyzing and various references to relevant theories including journals, articles and reports from previous researchers related to the research title. In the initial stage of collecting articles based on the variables contained in the title, namely Learning Media as an Alternative to Passion for Learning, from the many articles we found several articles that matched the title. At the article reduction stage, there were a number of articles that had to be discarded because they were less relevant to the title topic, for example the article only discussed passion or motivation for learning without mentioning the use of learning media as an alternative. Based on the results of the analysis and study sources obtained, it can be concluded that learning media is a means of communication between teachers and students in delivering learning material that is clearer and not monotonous, so that it can increase student learning motivation and increase learning success.